2005
DOI: 10.1002/j.2161-1882.2005.tb00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Outreach by College Counselors: Increasing Student Attendance at Presentations

Abstract: Psychoeducational outreach programming by college counselors can be an effective service to meet students' needs; however, getting students to attend outreach programs on a college campus can be challenging. The authors describe a model of an outreach series and the strategies implemented to increase student attendance at the presentations. Information collected from students through focus groups, a survey, and presentation evaluation forms revealed factors that seem to be important to increasing attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…In addition, the results of the experimental research similar to other studies (Allen, 1986;Handler, 2008;Marks & McLaughlin, 2005;and Snyder, 1998) in researching classroom management techniques (CAMTs and CARs) indicated improvement in student attendance (8.4%). This improvement reflects a positive significant correlation between the on-time attendance and overall grades through examining individual student's educational performance.…”
Section: Conclusion and Recommendationssupporting
confidence: 78%
“…In addition, the results of the experimental research similar to other studies (Allen, 1986;Handler, 2008;Marks & McLaughlin, 2005;and Snyder, 1998) in researching classroom management techniques (CAMTs and CARs) indicated improvement in student attendance (8.4%). This improvement reflects a positive significant correlation between the on-time attendance and overall grades through examining individual student's educational performance.…”
Section: Conclusion and Recommendationssupporting
confidence: 78%
“…In particular, the anonymity and convenience of web mental health resources may help promote greater information seeking among this population. As noted above, researchers have argued that CCWs are the most efficient means to communicate with students (Van Brunt, 2008) and can be a tool for disseminating information on outreach services (Marks & McLaughlin, 2005) as well as general health information (Hsiung, 1997). Surprisingly, although CCWs appear to offer numerous benefits, the first study examining the prevalence and nature of LGBT messages on these sites found that roughly 30% of these sites provided information on individual counseling services (Wright & McKinley, 2011).…”
Section: The College Counseling Centermentioning
confidence: 93%
“…Prior LGBT research stresses the importance of effective communications systems to serve the needs of LGBT students (Rankin, 2005). Indeed, prior mental health research examining CCWs praises their efficiency (Van Brunt, 2008), as well as their role in disseminating valued health information (Marks & McLaughlin, 2005) and their value in counseling (Van Brunt, 2008).…”
mentioning
confidence: 98%
“…Outreach activities around campus can bring health professionals, staff and students together to provide them all with evidence-based sleep knowledge and useful strategies. This would help address students' hesitation to seek help at student health services (Sanchez & King-Toler 2007;Marks & McLaughlin, 2005). Educating course instructors and professors about the negative impact for students who sacrifice sleep to meet assignment deadlines and study for exams is also important.…”
Section: Opportunities To Improve the Sleep Of Students Living In Resmentioning
confidence: 99%